Implementasi Hukum Kartu Kredit dalam Keuangan Syariah (Ditinjau dari Syariat Islam) - Rofiqoh, Relita; Patih, Husnama; Firnanda, Devi (Journal of Industrial and Syariah Economics, 2024)
This research aims to conduct an analysis of the implementation of contracts that can be used as a legal basis for credit card products in Sharia financial institutions. In Sharia banking, the definition of credit cards is regulated by DSN-MUI Fatwa No.42/DSN-MUI/V/2004 concerning Syariah Charge Card, and No. 54/DSN-MUI/X/2006is a tool that functions like a credit card is generally based on an existing system that has several parties concerned and is based on Sharia provisions. The use of descriptive qualitative research methods in the Systematic Literature Review. Data collection through references to scientific literature, books, and previous research. The research results show that there are many parties involved in the implementation of credit card transactions and have various differences of opinion regarding the use of credit cards the determination of the credit card contract is still debated among clerics. Determination of the contract is something that is said to be important because it is related to the law of whether a transaction is haram or halal and several contracts can be combined so that you can find the appropriate contract to use in transactions. There are six possible contracts implemented in sharia financial institutions, namely kafalah, hawalah, wakalah, qardh, ijarah, and murabahah.